Transmission of Toxoplasma gondii Infection Due to Bone Marrow Transplantation: Validation by an Experimental Model - Lopes, Carolina Salomão; Silva, Tamires Lopes; Almeida, Julio Cesar Neves de; Costa, Lucas Vasconcelos Soares; Mineo, Tiago Wilson Patriarca; Mineo, José Roberto (Frontiers in Medicine, 2019)
Toxoplasmosis is an opportunistic infectious disease and may present a fatal outcome for human bone marrow transplant (BMT) recipients, due to the rapid disease course in immunosuppressed individuals. Several reports about occurrence of toxoplasmosis after BMT have been published in the literature, but this disease has been associated mainly due to reactivation of latent infection rather than primary infection. Even though there are reports of acute toxoplasmosis in recipients who were seronegative for T. gondii, suggesting transmission of infection after BMT, the source of infection in those cases has not been clearly demonstrated, whether it is due to the transplantation procedure by itself or from environmental source. Thus, the present study aimed to observe if it could be possible to demonstrate the parasite`s ability to infect bone marrow (BM) cells and cause toxoplasmosis, when using an experimental model. Our results showed that 11% of hematopoietic and 7.1% of non-hematopoietic lineages may become infected when using in vitro experiments. Also, in vivo experiments demonstrated that, when C57BL/6 mice were infected with RH-RFP or ME-49-GFP T. gondii strains, the BM cells may be infected at different time points of infection. The parasites were detected by both fluorescent microscopy and qPCR. Also, when those BM samples were collected and used for BMT, the transplanted animals presented high rates of mortality and 87.5% of them became seropositive for T. gondii. Taken together, our results clearly demonstrated that it is possible to acquire primary T. gondii infection from the donor cells after BMT. Therefore, we are emphasizing that, before transplantation, serological screening for T. gondii infection from both donors and recipients, in addition to DNA search for this parasite from donor bone marrow cells, are necessary procedures to avoid the risk of T. gondii infection for immunocompromised patients.